Issues of the Professional Development of Investigators of Pre-Trial Investigation Agencies of the National Police of Ukraine - N. E. Miloradova (Law and Safety)
It has been noted that professional development of investigators of pre-trial investigation agencies of the National Police is a multi-faceted process, which includes both statutory regulated mandatory measures and appropriate professional and psychological support, as well as self-education and self-improvement of specialists. That is why consideration of the problems arising in the process of professional development and self-affirmation of employees of investigative units is a prerequisite for improving the efficiency of their activities. Legislative acts regulating the peculiarities of the professional development of investigators of the National Police of Ukraine have been considered.